Topographically Scattered Infrasound Waves Observed on Microbarometer Arrays in the Lower Stratosphere - Bird, E.J.; Lees, J.M.; Kero, J.; Bowman, D.C. (John Wiley and Sons Inc, 2022)
When an acoustic wave strikes a topographic feature, some of its energy is scattered. Sensors on the ground cannot capture these scattered signals when they propagate at high angles. We report observations of upwardly-scattered acoustic waves prior to refraction back to the ground, intercepting them with a set of balloon-borne infrasound microbarometers in the lower stratosphere over northern Sweden. We show that these scattered waves generate a coda whose presence can be related to topography beneath balloons and low-altitude acoustic ducts. The inclination of the coda signals changes systematically with time, as expected from waves arriving from scatterers successively closer to receivers. The codas are present when a temperature inversion channels infrasound from a set of ground chemical explosions along the ground, but are absent following the inversion's dissipation. Since scattering partitions energy away from the main arrival, these observations imply a mechanism of amplitude loss that had previously been inaccessible to measurement. As such, these data and results allow for a better comprehension of interactions between atmospheric infrasound propagation and the solid earth.